2021
DOI: 10.1001/jamaophthalmol.2020.6994
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Edema Resolution After Descemet Membrane Endothelial Keratoplasty for Fuchs Dystrophy Using Scheimpflug Tomography

Abstract: Predicting the extent of corneal edema resolution after Descemet membrane endothelial keratoplasty (DMEK) may help in preoperative decision-making by identifying patients who may benefit from restoring endothelial function.OBJECTIVE To develop and validate a predictive model for edema resolution after DMEK using Scheimpflug tomographic imaging. DESIGN, SETTING, AND PARTICIPANTSTwo prospective studies recruited participants with advanced Fuchs dystrophy at a university-based tertiary referral center between Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 36 publications
0
38
2
1
Order By: Relevance
“…In contrast, our model assessed tomography map patterns independent of preoperative CCT (Figure 4), and had much higher predictive power than the model by Zander and colleagues. 7 Our study is not without limitations. The limits of agreement for the validation group (Figure 1D) were wider than those of the derivation group (Figure 1B) because the model significantly underestimated the predicted change in CCT in 1 eye.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…In contrast, our model assessed tomography map patterns independent of preoperative CCT (Figure 4), and had much higher predictive power than the model by Zander and colleagues. 7 Our study is not without limitations. The limits of agreement for the validation group (Figure 1D) were wider than those of the derivation group (Figure 1B) because the model significantly underestimated the predicted change in CCT in 1 eye.…”
Section: Discussionmentioning
confidence: 84%
“…17 The strongest factor in the model proposed by Zander and colleagues was preoperative CCT; this is not surprising because change in CCT is calculated in part from preoperative CCT (i.e., these variables are related) and their model had few other candidate parameters. Indeed, when we applied the Zander model coefficient estimates (using standardized backscatter) 7 to our derivation data, we found that 70% (from R 2 ) of the predicted change in CCT was attributed to preoperative CCT (Figure 4), whereas in reality, only 15% (from R 2 ) of the observed change in CCT was explained by preoperative CCT (Figure 4).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations